Pathogenic Level of Reniform Nematode (Rotylenchulus reniformis Linford & Oliveira, 1940) on Tomato (Solanum lycopersicum L.) - Prerana Bhuyan; Gitanjali Devi (Archives of Current Research International, 2024)
Tomato is an important vegetable crop. Various plant parasitic nematode cause extensive damage during growth stage of tomato. Pathogenic level of Reniform nematode (Rotylenchulus reniformis), was investigated on tomato var. Pusa Ruby by inoculating 10, 100, 500, 1000, 5000 and 10000 nematodes per kg autoclaved soil. Observations on plant growth parameters and nematode numbers were recorded at 60 days following inoculation. The inoculated seedlings showed a progressive decrease in the plant growth parameters with increase in inoculum level of R. reniformis. Significant reduction in plant growth parameters were recorded at 1000 and above nematodes/kg soil. There was a gradual increase in the number of females, egg masses per root system, and nematode population of R. reniformis with increase in inoculum level. The rate of multiplication decreased with increase in the level of inoculation. The pathogenic level of R. reniformis was found to be 1000 nematodes per kg soil.